2015
DOI: 10.1242/dev.122044
|View full text |Cite
|
Sign up to set email alerts
|

Yap and Taz are required for Ret-dependent urinary tract morphogenesis

Abstract: Despite the high occurrence of congenital abnormalities of the lower urinary tract in humans, the molecular, cellular and morphological aspects of their development are still poorly understood. Here, we use a conditional knockout approach to inactivate within the nephric duct (ND) lineage the two effectors of the Hippo pathway, Yap and Taz. Deletion of Yap leads to hydronephrotic kidneys with blind-ending megaureters at birth. In Yap mutants, the ND successfully migrates towards, and contacts, the cloaca. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 30 publications
(47 reference statements)
3
48
0
1
Order By: Relevance
“…Taz NDϪ/Ϫ kidneys develop nor- mally, suggesting that YAP expression is sufficient in the absence of TAZ. However, silencing of Taz in Yap NDϪ/Ϫ mice severely worsens the phenotype, with kidneys being dysplastic, showing no ureters at E18.5, aberrant branching morphogenesis, blind-ending NDs, a defective ND-cloaca connection, and markedly increased apoptosis (48). These findings highlight the crucial role YAP and TAZ play in lower urinary tract development and lay the groundwork for further diagnostic, mechanistic, and therapeutic approaches to CAKUT.…”
Section: Kidney Developmentmentioning
confidence: 83%
See 2 more Smart Citations
“…Taz NDϪ/Ϫ kidneys develop nor- mally, suggesting that YAP expression is sufficient in the absence of TAZ. However, silencing of Taz in Yap NDϪ/Ϫ mice severely worsens the phenotype, with kidneys being dysplastic, showing no ureters at E18.5, aberrant branching morphogenesis, blind-ending NDs, a defective ND-cloaca connection, and markedly increased apoptosis (48). These findings highlight the crucial role YAP and TAZ play in lower urinary tract development and lay the groundwork for further diagnostic, mechanistic, and therapeutic approaches to CAKUT.…”
Section: Kidney Developmentmentioning
confidence: 83%
“…Astonishingly, Ret mutations are present in 30% of fetuses with bilateral or unilateral renal agenesis (59). Silencing of Yap in the ND in mice results in death within 24 h of birth due to severe anomalies of the kidney and urinary tract, including hydroureter and nephrosis (48). This phenotype mimics hyperactive Ret signaling accompanied by increased expression of Ret downstream target genes.…”
Section: Kidney Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, YAP and TAZ share some redundant functions, and both YAP and TAZ have been implicated in nephrogenesis [47][48][49] and in development of the urinary tract. 50 However, knockout of the YAP gene in mice leads to early embryonic lethality, 51 while knockout of TAZ induces development of renal cysts characteristic of polycystic kidney disease and lung abnormalities characteristic of emphysema. 47,48,52 In this study, we found upregulation of YAP but downregulation of TAZ expression in the diabetic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent genetic experiments in mice showed that ectopic expression of YAP (also known as YAP1) was sufficient to drive cell proliferation in liver, intestine, bronchus and skin Camargo et al, 2007;Dong et al, 2007;Schlegelmilch et al, 2011;Zhang et al, 2011a;Zhao et al, 2014). Surprisingly, YAP knockout mice have mild phenotypes, although they are deficient in proliferative repair of the intestine and resistant to intestinal tumour formation (Azzolin et al, 2014;Cai et al, 2010), as well as showing reduced bronchial stem cells (Zhao et al, 2014) and kidney defects (Reginensi et al, 2015). An important and widespread physiological role for YAP in mice might be obscured by the possibility of redundancy between YAP and TAZ (also known as WWTR1) a second mammalian family member that is highly similar in both sequence and function.…”
Section: Introductionmentioning
confidence: 99%